Risk factors in the development of postoperative complications after reconstructive surgery on the thoracic aorta - Alisa Krdžalić; Mustafa Tabaković; Ivana Iveljić; Ema Tahto; Goran Krdžalić (Medicinski glasnik, 2022)
Aim: To determine risk factors responsible for developing postoperative complications after the thoracic aorta reconstructive surgery. Methods: Medical records of 100 patients, who had undergone elective or emergency thoracic aorta reconstructive surgery at the Clinic for Cardiovascular Surgery, University Clinical Center Tuzla, were analysed. Intraoperative data as cross-clamp time (CCT), duration of cardiopulmonary bypass (CPBT) and hypothermic circulatory arrest time (HCAT) were evaluated. Univariate analysis was used to show risk factors for developing postoperative cardiac, respiratory, surgical and renal complications. Results: Between May 2019 and April 2021, 48 Bentall procedures (BP), 23 ascending aortic replacements (AAR), 20 BP and coronary artery bypass grafting (CABG) and 9 aortic valve replacements (AVR) with AAR were performed. Incidence of postoperative complications in the elective and emergency groups was as follows: respiratory 20% vs 38% (p=0.049), cardiac 18% vs 70% (p=0.015), renal 16% vs 48% (p=0.027) and surgical 4% vs 6% (p>0.05). Intrahospital 30 days morbidity was 44% with mortality rate of 13%. The results showed that CPBT>180 minutes was a risk factor for respiratory (p=0.034), cardiac (p=0.020) and renal (p=0.027) postoperative complications after acute type A aortic dissection surgery. Conclusion: CPBT > 180 min is a risk factor for postoperative development of respiratory, cardiac and renal complications. Postoperative cardiac and renal complications were associated with longer HCAT.
Keywords: aortic aneurysm; cardiopulmonary bypass; patient outcome assessment